Pengaruh Metode dan Strategi Tenaga Pendidik dalam Membentuk Karakter Anak Usia Dini - Ubaidillah (Atthiflah: Journal of Early Childhood Islamic Education, 2018)
Children are entrusted by God that we must guard and educate so that he becomes a useful human being. Every child is born together with the potential it has. Nothing escapes His Oversight and Concern. it is the duty of parents and teachers to be able to discover this potential. The condition is complete acceptance of the child's condition. In the field of education a child from birth requires appropriate services in meeting educational needs accompanied by an understanding of the characteristics of children in accordance with their growth and development will greatly assist in adjusting the learning process for children with their respective ages, needs, and conditions, both intellectually, emotionally and social. Early childhood is a golden period (golden age) for the development of children to obtain the educational process. This period is a valuable year for a child to recognize various kinds of facts in his environment as a stimulus to his personality, psychomotor, cognitive and social development. For this reason, early childhood education in the form of providing stimuli (stimulation) from the immediate environment is needed to optimize children's abilities. And the character of children must be formed from an early age. The goal of forming this character is that the child has a good personality so that when the child has reached adulthood, he will become a pious and pious child so that he will be able to provide benefits to others. Without the right process of providing care and education, it is impossible to produce children of character.